2017
DOI: 10.1111/maps.12877
|View full text |Cite
|
Sign up to set email alerts
|

Refractory materials in comet samples

Abstract: Transmission electron microscope examination of more than 250 fragments, >1 μm from comet Wild 2 and a giant cluster interplanetary dust particle (GCP) of probable cometary origin has revealed four new calcium‐aluminum‐rich inclusions (CAIs), an amoeboid olivine aggregate (AOA), and an additional AOA or Al‐rich chondrule (ARC) object. All of the CAIs have concentric mineral structures and are composed of spinel + anorthite cores surrounded by Al,Ti clinopyroxenes and are similar to two previous CAIs discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 100 publications
(323 reference statements)
1
47
0
Order By: Relevance
“…One of the most surprising findings of the Stardust comet sample return mission was the presence of fragments of chondrules, AOAs, and CAIs in the comet Wild 2, that must have formed in the inner solar system (Simon et al 2008;Bridges et al 2012;Joswiak et al 2017). It is estimated that 0.5 vol% of the sample return material is CAIs (Joswiak et al 2017). This is comparable to the abundance in CM and CR chondrites formed in our model at about 4 AU, despite the fact that comets are presumed to form much further out in the disk, at tens of AU.…”
Section: Cais In Cometsmentioning
confidence: 99%
“…One of the most surprising findings of the Stardust comet sample return mission was the presence of fragments of chondrules, AOAs, and CAIs in the comet Wild 2, that must have formed in the inner solar system (Simon et al 2008;Bridges et al 2012;Joswiak et al 2017). It is estimated that 0.5 vol% of the sample return material is CAIs (Joswiak et al 2017). This is comparable to the abundance in CM and CR chondrites formed in our model at about 4 AU, despite the fact that comets are presumed to form much further out in the disk, at tens of AU.…”
Section: Cais In Cometsmentioning
confidence: 99%
“…Comets consist of a mixture of refractory materials in the classical sense (minerals), an organic "soup" that ranges from simple molecules more volatile than water ice, such as methane and methanol, to heavy and refractory molecules such as kerogen-like insoluble organic matter (IOM), and a number of frozen volatiles (ices) like H 2 O, CO 2 , CO, H 2 S, NH 3 , and multiple other minor species (Bockelée-Morvan et al 2004;Mumma and Charnley 2011;. Comet nuclei have a very low density/high porosity (Weissman et al 2004;Weissman and Lowry 2008;, and the few samples available on Earth that likely originate from comets (chondritic-porous interplanetary dust particles, ultra-carbonaceous Antarctica micro-meteorites), as well as grains collected in the coma of 81P/Wild by the Stardust mission, all exhibit a very fine-grained texture (Joswiak et al 2017). These compositional and physical characteristics point to a rather slow and gentle accretion under cold conditions 100 K, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Joswiak et al. () found that calcium‐aluminum‐rich inclusion (CAI)‐like fragments account for ≈1 vol% in cometary samples including Wild 2 and a giant cluster IDP named U2‐20GCP. Joswiak et al.…”
Section: Discussionmentioning
confidence: 99%
“…Joswiak et al. () make a strong case that U2‐20 has a cometary origin, and have noted (personal communication) that it has coarse‐grained rocks (CAI‐like) in direct contact with FGM including GEMS and EAs. Wooden et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation